A2 liver transplantation across the ABO barrier: Increasing options in the donor pool?. Issue 6 (2nd January 2018) - Ge, Jin; Roberts, John P.; Lai, Jennifer C.
Abstract : Watch a video presentation of this article Watch the interview with the author